Comparison of the effects of erythropoietin and anakinra on functional recovery and gene expression in a traumatic brain injury model - Anderson, Gail D.; Peterson, Todd; Vonder Haar, Cole; Farin, Fred M.; Bammler, Theo K.; Kantor, Eric D.; MacDonald, James W.; Hoane, Michael R. (Frontiers in Pharmacology, 2013)
The goal of this study was to compare the effects of two inflammatory modulators, erythropoietin (EPO) and anakinra, on functional recovery and brain gene expression following a cortical contusion impact (CCI) injury. Dosage regimens were designed to provide serum concentrations in the range obtained with clinically approved doses. Functional recovery was assessed using both motor and spatial learning tasks and neuropathological measurements conducted in the cortex and hippocampus. Microarray-based transcriptional profiling was used to determine the effect on gene expression at 24 h, 72 h and 7 days post-CCI. Ingenuity Pathway Analysis was used to evaluate the effect on relevant functional categories. EPO and anakinra treatment resulted in significant changes in brain gene expression in the CCI model demonstrating acceptable brain penetration. At all three time points, EPO treatment resulted in significantly more differentially expressed genes than anakinra. For anakinra at 24 h and EPO at 24 h, 72 h and 7 days, the genes in the top 3 functional categories were involved in cellular movement, inflammatory response and cell-to-cell signaling. For EPO, the majority of the genes in the top 10 canonical pathways identified were associated with inflammatory and immune signaling processes. This was true for anakinra only at 24 h post-traumatic brain injury (TBI). The immunomodulation effects of EPO and anakinra did not translate into positive effects on functional behavioral and lesion studies. Treatment with either EPO or anakinra failed to induce significant beneficial effects on recovery of function or produce any significant effects on the prevention of injury induced tissue loss at 30 days post-injury. In conclusion, treatment with EPO or anakinra resulted in significant effects on gene expression in the brain without affecting functional outcome. This suggests that targeting these inflammatory processes alone may not be sufficient for preventing secondary injuries